PENGARUH APLIKASI SISTEM OLAH TANAH TERHADAP KEUNTUNGAN USAHATANI JAGUNG DI DESA BUNUT BAOK KECAMATAN PRAYA KABUPATEN LOMBOK TENGAH - Hayatunnufus, Baiq Indah; Budastra, I Ketut; Yakin, Addinul (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2023)
The results showed; (1) The difference in the average cost of corn tillage farming Rp 10.922.844/Ha and the average cost of corn no-tillage farming Rp. 7.504.691. (2) The difference in the average income in corn tillage farming is Rp. 21,696,671 and the average income of corn no-tillage farming is Rp. 14,465,580. (3) The difference in the average efficiency of corn tillage farming is 1,85 and the average efficiency of corn no-tillage farming is 1,49, indicating that both farms are feasible. (4) The difference in the average profit of corn tillage farming is Rp 9.380.233/Ha and the average profit of corn no-tillage farming is Rp 3.141.975/Ha. Based on the profit function analysis, it is known that the factors that significantly influence the profit of tilled corn are dummy tillage – no-tillage. Variables that do not have a significant effect are selling prices, fertilizer, pesticides, and labor.